2020
DOI: 10.1038/s41598-020-63470-1
|View full text |Cite
|
Sign up to set email alerts
|

SWATH-MS-based quantitative proteomics reveals a uniquely intricate defense response in Cnaphalocrocis medinalis-resistant rice

Abstract: Cnaphalocrocis medinalis is a major insect pest of rice in Asia. A few defensive enzymes were reported to show higher activities in a resistant rice line (Qingliu) than in a susceptible rice line (TN1) upon leaffolder infestation. However, the overall molecular regulation of the rice defense response against leaffolder herbivory is unknown. Here, differential proteomic analysis by SWATH-MS was performed to identify differentially expressed proteins between the two rice varieties, Qingliu and TN1, at four time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…An opposing theory states that plants suppress photosynthesis to conserve energy and reduce food supply to pathogens. Photosynthesis is enhanced by Xoo (Sana et al 2010;Li et al 2012a), insect (Liu et al 2016;Cheah et al 2020), and M. oryzae infection in the biotrophic stage (Azizi et al 2019) but suppressed by the necrotrophic fungus R. solani (Lee et al 2006;Karmakar et al 2019) and viral infection (Xu et al 2013). Therefore, photosynthetic activity varies depending on the feeding style of the pathogen, which is consistent with the response in other species (for review Chen et al 2019).…”
Section: Common Metabolites and Specific Metabolites Upon Each Bioticsupporting
confidence: 55%
See 4 more Smart Citations
“…An opposing theory states that plants suppress photosynthesis to conserve energy and reduce food supply to pathogens. Photosynthesis is enhanced by Xoo (Sana et al 2010;Li et al 2012a), insect (Liu et al 2016;Cheah et al 2020), and M. oryzae infection in the biotrophic stage (Azizi et al 2019) but suppressed by the necrotrophic fungus R. solani (Lee et al 2006;Karmakar et al 2019) and viral infection (Xu et al 2013). Therefore, photosynthetic activity varies depending on the feeding style of the pathogen, which is consistent with the response in other species (for review Chen et al 2019).…”
Section: Common Metabolites and Specific Metabolites Upon Each Bioticsupporting
confidence: 55%
“…Studies on the response of rice to other insects have also revealed specific responses. The response of a resistant rice line (cultivar Qingliu) to rice leafroller (Cnaphalocrocis medinalis) involved the activation of the Calvin cycle and the light reaction of photosynthesis, followed by the biosynthesis of amino acids and other metabolites (Cheah et al 2020). Furthermore, resistance was determined by flavonoid biosynthesis at a specific rate and time.…”
Section: Response Of Rice To Insectsmentioning
confidence: 99%
See 3 more Smart Citations